Improved procedures for the cleavage and reduction of GDGTs for hydrogen isotope analysis - C.D. Rosendahl; X. Zhao; A.E. Maloney; J.M. McFarlin; K.J. Keller; R. Kreutz; J. Altun; L.H. Bachmann; J. Hartmann; H.K. Batther; A.N. Calhoun; M. Elvert; et al. (Organic Geochemistry, 2026)

A bioactive chlorophyll-derived yellow phyllobilin from senescent leaves of Carica papaya (Caricaceae) and its potential role in the ethnopharmacological use of withered leaf extracts - Christian Elvert; Rao Zhigang; Oriol Ruiz-Catalan; Johanna M. Gostner; Andreas Koeberle; Cornelia Karg; Awodayo O. Adepiti; Simone Moser (Phytochemistry Letters, 2025)

Soothsaying DOM: A Current Perspective on the Future of Oceanic Dissolved Organic Carbon - Sasha Wagner; Florence Schubotz; Karl Kaiser; Christian Hallmann; Hannelore Waska; Pamela E. Rossel; Roberta Hansman; Marcus Elvert; Jack J. Middelburg; Anja Engel; Thomas M. Blattmann; Teresa S. Catalá; et al. (Frontiers in Marine Science, 2020)

Degradation of macroalgal detritus in shallow coastal Antarctic sediments - U. Braeckman; F. Pasotti; S. Vázquez; K. Zacher; R. Hoffmann; M. Elvert; H. Marchant; C. Buckner; M. L. Quartino; W. Mác Cormack; K. Soetaert; F. Wenzhöfer; et al. (Limnology and Oceanography, 2019)
Glaciers along the western Antarctic Peninsula are retreating at unprecedented rates, opening up sublittoral rocky substrate for colonization by marine organisms such as macroalgae. When macroalgae are physically detached due to storms or erosion, their fragments can accumulate in seabed hollows, where they can be grazed upon by herbivores or be degraded microbially or be sequestered. To understand the fate of the increasing amount of macroalgal detritus in Antarctic shallow subtidal sediments, a mesocosm experiment was conducted to track 13 C‐ and 15 N‐labeled macroalgal detritus into the benthic bacterial, meiofaunal, and macrofaunal biomass and respiration of sediments from Potter Cove (King George Island). We compared the degradation pathways of two macroalgae species: one considered palatable for herbivores (the red algae Palmaria decipiens ) and other considered nonpalatable for herbivores (the brown algae Desmarestia anceps ). The carbon from Palmaria was recycled at a higher rate than that of Desmarestia , with herbivores such as amphipods playing a stronger role in the early degradation process of the Palmaria fragments and the microbial community taking over at a later stage. In contrast, Desmarestia was more buried in the subsurface sediments, stimulating subsurface bacterial degradation. Macrofauna probably relied indirectly on Desmarestia carbon, recycled by bacteria and microphytobenthos. The efficient cycling of the nutrients and carbon from the macroalgae supports a positive feedback loop among bacteria, microphytobenthos, and meiofaunal and macrofaunal grazers, resulting in longer term retention of macroalgal nutrients in the sediment, hence creating a food bank for the benthos.

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Impact of IVC housing on emotionality and fear learning in male C3HeB/FeJ and C57BL/6J mice - Magdalena Kallnik; Ralf Elvert; Nicole Ehrhardt; Daniela Kissling; Esther Mahabir; Gerd Welzl; Theresa Faus-Kessler; Martin Hrabé de Angelis; Wolfgang Wurst; Jörg Schmidt; Sabine M. Hölter (Mammalian Genome, 2007)

The microbial community structure of different permeable sandy sediments characterized by the investigation of bacterial fatty acids and fluorescence in situ hybridization - S. I. Bühring; M. Elvert; U. Witte (Environmental Microbiology, 2005)
Summary This study describes the microbial community structure of three sandy sediment stations that differed with respect to median grain size and permeability in the German Bight of the Southern North Sea. The microbial community was investigated using lipid biomarker analyses and fluorescence in situ hybridization. For further characterization we determined the stable carbon isotope composition of the biomarkers. Biomarkers identified belong to different bacterial groups such as members of the Cytophaga‐Flavobacterium cluster and sulfate‐reducing bacteria (SRB). To support these findings, investigations using different fluorescent in situ hybridization probes were performed, specifically targeting Cytophaga‐Flavobacterium , γ‐Proteobacteria and different members of the SRB. Depth profiles of bacterial fatty acid relative abundances revealed elevated subsurface peaks for the fine sediment, whereas at the other sandy sediment stations the concentrations were less variable with depth. Although oxygen penetrates deeper into the coarser and more permeable sediments, the SRB biomarkers are similarly abundant, indicating suboxic to anoxic niches in these environments. We detected SRB in all sediment types as well as in the surface and at greater depth, which suggests that SRB play a more important role in oxygenated marine sediments than previously thought.